Euthanasia and assisted suicide . Comparison of regulations in Poland and Switzerland with consideration of selected practical aspects - Gęsiak, Katarzyna (The phenomenon of euthanasia: Philosophy – Culture – Medicine – Law, 2025)
The study presents differences in the legal regulation of euthanasia and assisted suicide in Switzerland and Poland. In Switzerland, euthanasia is generally prohibited, but the decriminalization of assistance in the suicide of another person has been adopted in cases where the helper is guided by non-selfish motives. The specific interpretation of this premise excluding criminal liability allows for the open operation in Switzerland of organizations that provide their clients with assistance in suicide for a fee. However, the decriminalization of assisted suicide has a negative impact on the work of Swiss palliative medicine physicians. The Polish legislator penalizes both euthanasia and assistance in the suicide of another person, regardless of the motivation of the helper. However, police statistics from 1999-2023 indicate an increase in the number of proceedings initiated concerning the crime of assistance in suicide (Article 151 of the Penal Code) compared to the end of the 1990s. The number of assistance in suicides, which were identified by the Police, has also increased.